New Perspectives on the Efficacy of Catgut Embedment in Acupoint Combined with Rehabilitation Training for Pediatric-Cerebral-Palsy Motor Function Disorders: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Hu, Zhe-Hao; Zhang, Xin-Yue; Jiang, Hong-Zhan; Li, Xue-Jing; Hao, Yu-Fang (Healthcare (Basel), 2025)
Background: Motor Function Disorders (MFDs) are common conditions in children with cerebral palsy and closely related to muscle spasticity. Catgut Embedment in Acupoint (CEA) has shown promise as an important adjunctive therapy but current evidence remains insufficient. The aim of this study was to evaluate the efficacy and safety of CEA in Pediatric-Cerebral-Palsy Motor Function Disorders (PCPMFDs). Methods: PubMed, Cochrane Library, Embase, Web of Science, four Chinese databases and two clinical trial registries were searched to include randomized controlled trials of patients with PCPMFDs treated with CEA combined with conventional rehabilitation. Meta-analysis was performed using Review Manager 5.4, Stata 18 and R Studio software 2025, and risk of bias was assessed for the included studies using the Cochrane Collaboration Network tool. Results: A total of 17 papers were included, including 1106 PCPMFDs patients with a wide range of conditions, age ≤ 9 years, and rehabilitation training mostly using Bobath/Vojta therapy. Meta-analysis showed that CEA was effective in improving MFDs with the Gross Motor Function Measure Scale (SMD, 0.90 [95% CI, 0.57 to 1.23], p < 0.0001) and the modified Ashworth Scale (MD, −0.40 [95% CI, −0.58 to −0.23], p < 0.0001). Preliminary results suggested that a treatment regimen, which consisted of three monthly sessions and lasted for one to two months, was most effective. Conclusions: CEA is an effective complementary treatment for patients with PCPMFDs with mild adverse effects. However, due to the relatively new perspective of this study, only a small number of researchers have focused on this area and conducted studies, resulting in fewer included studies meeting requirements, which is a direct result of the fact that this study, although informative, still requires a significant amount of research before clear evidence-based recommendations can be developed.